The sources of the Kuznets relationship between the road deaths to road injuries ratio and economic growth - Sirajudeen, Abdurrasheed Olayinka; Law, Teik Hua; Wong, Shaw Voon; Jakarni, Fauzan Mohd; Ng, Choy Peng (Elsevier, 2021)
Introduction: Past empirical studies indicated that there is a Kuznets or reverse U-shaped relationship between road deaths and per capita income, such that the number of road death increases at a low level of per capita reverse U-shaped relationship was observed between road injuries and per capita income. While these studies explored the impact of per capita income on road deaths and road injuries, no studies have examined the relationship between per capita income and road death to road injury ratio (DPI). Method: Using a fixed effects panel regression analysis from 67 countries spanning over a period of five decades (1960–2013), the present study sought to explore the impact of per capita gross domestic product (per capita GDP) on the DPI ratio and the underlying factors responsible for the relationship. Results: Our result suggests that per capita GDP followed a reverse U-shaped relationship with DPI. Moreover, the relative improvements in higher mobility roads as compared to improvements in higher accessibility roads, motorcycle ownership to passenger car ownership ratio, percentage of population living in an urban area, infant mortality rate, and the percentage of population below 15 years of age and above 64 years of age contributed to this relationship. Practical Applications: This implies that, at lower level of economic growth where road deaths exceed road injuries, countries should implement low-cost measures to combat road deaths cases. Such measures include mandating wearing of quality helmets and daytime running headlights for motorcycles. On the other hand, at higher level of economic growth where road injuries surpass road deaths, countries are encouraged to devote more resources to improving medical technology and services to treat road injury victims, mandating seatbelt use, as well as enhancing and promoting public transportation service.